The use of didactic resources applied in the communicative approach, in teaching learning process of english language, in “mons. Alberto Zambrano” high school of Olmedo city. 2010-2011 - Jiménez Gaona, Flavio Fernando (2011)
The research about “The Use of Didactic Resources applied in the Communicative Approach, in Teaching-Learning Process of English Language, in Mons. Alberto Zambrano High school of Olmedo city during 2010-2011” was performed to describe how this curricular component affects the teaching-learning process of the English language in students of this educational center. The study is focused in the use of instructional materials applied in the communicative approach for English teaching and it was directed to 369 students and 3 teachers of Mons. Alberto Zambrano High school. In the bibliographical analysis of this research we used the deductive method, to collect data we applied the survey technique which was applied to a sample of 57 students and 3 English teachers who helped us to fulfill this work. To analyze and interpret the information we employed the inductive and descriptive methods. The final report was constructed by using the descriptive method too. As a result of the research, we found that this institution does not have enough didactic resources available for English teaching; conventional methodology predominates over communicative one. Most of applied materials are also conventional; new information and communication technologies are not still used in English teaching and students’ achievements in English are also limited. Communicative approach conceptualization is incomplete in teachers and its application is limited by the little use of instructional materials. The textbook is the most used instructional material; it helps in teaching learning process of English language and it is also highly accepted in teachers as well as in students. According to the present work, the main problems that limit the teaching learning process at the researched institution are the limited instructional material, wide contents, high number of students and little students’ motivation. Eventually, we formulated the respective recommendations and suggestions.